Study on the burning Practices Developed by Rural Producers in the Municipality of São João do Sóter, Maranhão (Research, Society and Development, 2020)
Fires are related to land use, I am a source of change and an important modeling agent of ecosystems and it is a cultural practice where many families of this technique for preparing the land for planting for family livelihood, its harm is little known for its population. In this sense, the study aimed to carry out data on the burning practices developed by rural producers in the village of Santa Maria in the municipality of São João do Sóter-MA. Data collections were performed using semi-open questionnaires and on-site observations to support the results. We interviewed 100 heads, 86% of the population has lived in the village for more than 40 years and 47% over the age of 60, 42% had incomplete elementary schooling, 96% of the families live in houses with mud structures and 48% of families are made up of four to six residents. 80% of families have subsistence agricultural activities. 99% burn the land for agricultural production, 62% produce charcoal from babassu coconut shells and 38% forest wood. 100% of respondents reported this problem and also predatory hunting. The burning practices is a cultural activity of the population, it is the main work tool in agriculture. The present study contributed to the provision of data that can assist in the elaboration of strategies in the management of fires in rural activities.